Spot para radioblog: uma proposta de multiletramentos em sala de aula. - Soares, Luciana Guimarães (2018)
The research Project at hand was aimed at the production of publicity ads – Spot – instantiated in audio files, podcasts, to be placed in radioblogs as a way of developing competence on reading, writing and speaking for students at the 9th year on Elementary School. We’ve opted for a study which could contemplate three aspects: Language, Culture and Technology for the composition of a Didactic Prototype that could be able to help on pedagogical practices aimed at the multiliteracy of our students. Another bias guiding this task is the teaching of the language ruled by the textual genres, with the objective of improving the speech, textual and linguistic practices of the pupils, starting from the use and reflection upon different musical expressions for the composition of audio files – spot for radioblog. Furthermore, we also aimed to minimize the gaps existing on school practices concerning the teaching of the oral genres, with the different levels of formality, which meet the needs of a society increasingly multimodal and multisemiotic. Our proposal in interveining was based on various theoretical assumptions, from which we highlight Rojo (2012), Marcuschi (2002, 2008), Coscarelli (2014), Dolz and Schneuwly (2004), Bezerra (2017). As this study’s final product, we present the radioblog Acorde na Sala, backing up the spot genre, tied to the Internet. The audio files are the result of the reflection of these young pupils about musical and/or cultural preferences and the school’s need of promoting a channel where the students are able to express in a critical and autonomous form, by speech or writing, on school context and beyond that.